Assessing the compliance on public procurement act no.7 of 2011 and it’s regulations on road construction projects in Tanzania Local Government Authorities (TLGAs): A case of selected LGAS in Dodoma region - Matembo, Fridolin (Mzumbe University, 2024)
A Dissertation Submitted in partial Fulfillment of the Requirements for the award of the Degree of Master of Science in Procurement and Supply Chain Management (Msc - PSCM) of Mzumbe University 2016